The role of external factors on the reactivation of the heritage language of Turkish-German returnees - Antonova-Unlu, Elena; Bayram, Fatih (Frontiers in Psychology, 2023)
This study investigates the heritage language performance of Turkish-German returnees upon their return to Turkey and the influence of external factors on their proficiency in the (re-)activated heritage language (HL). Data were collected from 28 Turkish heritage speakers who grew up in Germany and later returned to Turkey, alongside a control group of monolingual speakers. Both groups completed two language tasks: a cloze test and an error correction task. The results revealed group differences between the returnees and the control group, as well as considerable individual variability within the returnee group. In examining the individual variation and their relative dependence on external factors through random forest analysis, the length of residence in Germany, the age at which participants returned to Turkey, and the frequency of Turkish language use in their migration context were found to be significant predictors of the returnee participants' performance in their (re-)activated HL. Formal contact with the dominant German language did not exert a substantial impact on the returnees' language proficiency.